2021
DOI: 10.1016/j.clnu.2020.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal human milk macronutrients, body composition and infant appetite during early life

Abstract: Background & aims: Breastfeeding is the gold standard infant feeding. Data on macronutrients in relation to longitudinal body composition and appetite are very scarce. The aim of this study was to investigate longitudinal human milk macronutrients at 1 and 3 months in association with body composition and appetite during early life in healthy, term-born infants. We hypothesized that infants receiving higher caloric human milk would have more body fat mass and satiate earlier. Methods: In 133 exclusively breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 38 publications
4
38
0
Order By: Relevance
“…The third study showed no difference in both subcutaneous-abdominal and preperitoneal fat thicknesses between breastfed and formula-fed infants [ 13 ]. The most recent study investigated the effect of HM macronutrient composition reporting positive relationships between HM fat concentration (measured in post-feed sample which is the most varied between women and feeds) and infant subcutaneous-abdominal fat thickness, and negative between protein concentration and VF thickness [ 15 ]. These results suggest independent regulation of the visceral and subcutaneous-abdominal fat depots in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third study showed no difference in both subcutaneous-abdominal and preperitoneal fat thicknesses between breastfed and formula-fed infants [ 13 ]. The most recent study investigated the effect of HM macronutrient composition reporting positive relationships between HM fat concentration (measured in post-feed sample which is the most varied between women and feeds) and infant subcutaneous-abdominal fat thickness, and negative between protein concentration and VF thickness [ 15 ]. These results suggest independent regulation of the visceral and subcutaneous-abdominal fat depots in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the duration of exclusive breastfeeding was found to relate positively to percentage fat mass (%FM) and subcutaneous, but not VF [ 14 ], with maternal factors having no effect on development of these fat depots; however, infants were followed up to 6 months only, with 38% exclusively breastfed at 3 months of age (19% at 6 months). The only study that investigated effect of HM macronutrient composition on infant abdominal adiposity showed positive relationships between HM fat concentration and infant abdominal subcutaneous fat thickness, but negative between protein concentration and VF thickness [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of human milk was comparable to that reported in previous studies. [20][21][22] We used mid-infrared spectrophotometer that was specifically developed for the evaluation of human milk and calibrated to human milk values for analysing the milk macronutrients and energy content. 23 In this study, fat was the most variable macronutrient in human milk, which is consistent with the literature on mature milk.…”
Section: Human Milk Macronutrientsmentioning
confidence: 99%
“…Breastfeeding mothers were instructed to collect hind milk samples, thus after their infants were breastfed, at infant’s age of 3 months as described before [ 26 ]. For 61 exclusively breastfed infants, human milk samples were analyzed for macronutrient composition (fat, energy, carbohydrate and protein).…”
Section: Methodsmentioning
confidence: 99%
“…Human milk macronutrient composition could potentially influence appetite-regulating hormone levels in BF infants as we previously found that exclusively BF infants-receiving human milk with higher fat and energy were satiated earlier. This could be a self-regulatory mechanism to prevent intake of excessive macronutrients [ 26 ]. Associations between ARH and human milk macronutrients and infant appetite until age 6 months, a critical window for adiposity programming as mentioned above, are lacking.…”
Section: Introductionmentioning
confidence: 99%